ILLNESS AND THE USE OF PSYCHOACTIVE DRUGS AMONG NURSING WORKERS AT INTENSIVE CARE UNITS - Tainara Genro Vieira; Carmem Lúcia Colomé Beck; Caliandra Marta Dissen; Silviamar Camponogara; Mariangela Gobatto; Alexa Pupiara Flores Coelho (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976927538 Aim: to identify the disease and use of psychoactive drugs among nursing staff of the Intensive Care Unit. Method: A descriptive study with a quantitative approach, performed in the Pediatric Intensive Care Units, Neonatal and Adult of a teaching hospital in the second half of 2011, with the participation of 49 nursing staff. The instrument was self-administered questionnaire with analysis by simple descriptive statistics. Results: 28.5% of employees use psychoactive medication, 24.4% of these reported that the drugs were prescribed. 24.4% of the subjects have any mental illness, the most cited depression with 14.2%. The shift was evident that most workers with mental illness was the night with 43.7%. Still, 63.2% of workers reported that self-treatment using antidepressant drugs with 12.2%. Conclusion: it is necessary to create strategies that avoid the illness, the use of psychoactive drugs and self-medication by health workers.